Ocular toxicities of targeted therapies and immunotherapies in hematologic malignancies - Aqil, Mohammad S.; Al-Marrawi, Yzen; Yaldo, Marcus; Abu-Mahfouz, Ahmad; Singh, Lavi; Gopishetty, Swathi; Idogun, Precious; Ezekwudo, Daniel; Jaiyesimi, Ishmael; Weiner, Adam J. (Frontiers in Oncology, 2026)
Targeted therapies and immune-based treatments have transformed the management of hematologic malignancies. However, these agents can also result in unintended ocular adverse effects. These toxicities are often underrecognized but may significantly affect patient quality of life and therapeutic decision-making. A comprehensive understanding of these effects is essential for interdisciplinary management. This review synthesizes the current evidence regarding ocular toxicities associated with modern targeted and immune therapies used in hematologic cancers. Data were drawn from case reports, clinical trials, observational studies, and pharmacovigilance databases. Ocular side effects were reported across all major therapy classes, including cell therapies, kinase inhibitors, immune checkpoint inhibitors, monoclonal antibodies, antibody–drug conjugates, and proteasome inhibitors. Chimeric antigen receptor T-cell therapies commonly induce neuro-ophthalmic symptoms such as photophobia and visual disturbances, frequently in association with neurotoxicity syndromes. Tyrosine kinase inhibitors were associated with a range of effects, including periorbital edema, uveitis, and retinal vascular complications. Immune checkpoint inhibitors caused inflammatory eye diseases such as uveitis, optic neuritis, and ocular myasthenia, consistent with immune-related adverse events. Certain antibody–drug conjugates, particularly those used in multiple myeloma, produced high rates of ocular surface disease that required dose modifications. While many adverse effects were reversible, some caused vision-threatening complications that required prompt ophthalmologic intervention. Pediatric-specific data were sparse, and long-term ocular outcomes remain poorly defined. Ocular toxicities from modern hematologic cancer therapies span a broad clinical spectrum and vary by drug class. Increased awareness of these complications among oncologists and ophthalmologists can support earlier detection and treatment. Accurate clinical descriptions of ocular adverse events and effective management recommendations in these settings will help improve patient outcomes and their quality of life.